Two‐ and Three‐Dimensional Transthoracic Echocardiography in the Assessment of Acquired Ascending Aortic Aneurysm to Pulmonary Artery Fistula. Issue 9 (30th July 2013) - Roomi, Asad Ullah; Kemaloglu Oz, Tugba; Williams, Shammah O.; Nanda, Navin C.; Mehta, Kruti J.; Sungur, Aylin; McGiffin, David C.
<x xml:space="preserve">Abstract</x> Aorta to pulmonary artery fistula is an uncommon and potentially fatal condition. This case is of a 48‐year‐old Caucasian male with congestive heart failure and multiple aortic valve replacement surgeries who presented with an acquired ascending aortic aneurysm to pulmonary artery fistula diagnosed using two‐dimensional transthoracic echocardiography via nonstandard imaging windows. Three‐dimensional transthoracic echocardiography using live/real time three‐dimensional color Doppler was used to assess the size of the opening of the fistula, providing additional value. This patient was surgically managed and is doing well 8 months postoperation.